Neue Inschriften aus Bilecik 1 - Hüseyin Uzunoğlu; Nalan Eda Akyürek Şahin (Gephyra, 2022)
This article primarily introduces new inscriptions found in Bilecik province, most of which are preserved today in Bilecik Museum, although, some inscriptions remain in the field. The remaining inscriptions in the museum are to be published in another article in the next issue of this journal, which we are preparing as the continuation of this article.Bilecik Museum, the foundation of which began in 2005 and which was officially opened in 2010, is one of Turkey’s new museums. Due to the large number of stone artifacts found in the area, a museum was needed to preserve and display them. Most of the works in the Bilecik Museum are a collection compiled from the towns and villages of Bilecik. However, during the foundation of the museum, artifacts were also brought to it from the surrounding museums such as Kütahya and Afyon. However, some of them do not belong culturally to the Bilecik region, see. e.g. here no. 1, 7, 23-27. We also recorded inscriptions in a small museum in Söğüt, a town of Bilecik, in the Söğüt Museum at that time, and we are now publishing them here in this paper, as these stones were later transported from Söğüt to the Bilecik Museum. Today, the region belonging to the province of Bilecik was largely within the territory of the ancient city of Nikaia. The inscriptions of Nikaia and its surroundings were published by the late Prof. Dr. Sencer Şahin (I.Nikaia) between 1978-1987 in 5 volumes. During the foundation of the Bilecik Museum in 2005, the museum administration at that time consulted with Prof. Sencer Şahin in order that he could transcribe and translate the many inscriptions into Turkish. Sencer Şahin commissioned me (N. Eda Akyürek Şahin) with examining these inscriptions and translating them into Turkish. For this purpose, many artefacts, both those brought to the museum and those that were still in the field and recorded by the museum authorities, were transcribed and studied by me and their translations were provided to the museum. Later, for a few years (e.g. 2010-2011, 2013), I conducted epigraphic research in the Bilecik Museum with the permission of the Ministry of Culture and the museum directorate, including field research in the region under the permission and supervision of the museum authorities. This because at that time it was understood that these artefacts were going to be transported from the field to the museum, but unfortunately most of them remained in the field.Bilecik is very rich in terms of its inscriptions. The general character of the region was rural and consisted of villages and farms. However, the density of the finds shows that this region was densely populated at that time. It is seen that the inscriptions are mainly divided into two groups, votive inscriptions and funerary inscriptions. The names of many gods are mentioned in the inscriptions. The artifacts are typologically in the form of prism-shaped altars or stelae with pediments. While altars are mostly preferred as votive stones, we see the stele are usually tombstones. Apart from these, there are also inscribed tombstones in the form of an architrave (see no. 41-42). At that time these architraves probably stood on great altars. Numerous personal names are documented in the inscriptions. All of the inscriptions belong to the Roman Imperial Period. There are quite a few inscriptions containing the surname Aurelius. Artifacts without inscriptions or whose inscriptions are not visible today are also included in this article in order to be known in the scientific world (nos. 61-78). In addition, photographs of previously published artifacts that are currently preserved in the museum (including the 3 altars standing today in the garden of the Bilecik Gendarmerie) have been added to the end of the article. These inscriptions were previously in the field and most of them were first published by Sencer Şahin.